The effect of boson–boson interaction on the bipolaron formation. (1st October 2022) - Jager, J; Barnett, R
Abstract: Impurities immersed into a surrounding ultra-cold Bose gas experience interactions mediated by the surrounding many-body environment. If one focuses on two impurities that are sufficiently close to each other, they can form a bipolaron pair. Here, we discuss how the standard methods based on linearizing the condensate field lead to results only valid in the weak coupling regime and for sufficiently large impurity separations. We show how those shortcomings can be remedied within the Born–Oppenheimer approximation by accounting for boson–boson interactions already on the mean-field level.